Comparison Analysis of Coal Biodesulfurization and Coal’s Pyrite Bioleaching with Acidithiobacillus ferrooxidans - Fen-Fen Hong; Huan He; Jin-Yan Liu; Xiu-Xiang Tao; Lei Zheng; Yi-Dong Zhao (The Scientific World Journal)
Acidithiobacillus ferrooxidans (A. ferrooxidans) was applied in coal biodesulfurization and coal’s pyrite bioleaching. The result showed that A. ferrooxidans had significantly promoted the biodesulfurization of coal and bioleaching of coal’s pyrite. After 16 days of processing, the total sulfur removal rate of coal was 50.6%, and among them the removal of pyritic sulfur was up to 69.9%. On the contrary, after 12 days of processing, the coal’s pyrite bioleaching rate was 72.0%. SEM micrographs showed that the major pyrite forms in coal were massive and veinlets. It seems that the bacteria took priority to remove the massive pyrite. The sulfur relative contents analysis from XANES showed that the elemental sulfur (28.32%) and jarosite (18.99%) were accumulated in the biotreated residual coal. However, XRD and XANES spectra of residual pyrite indicated that the sulfur components were mainly composed of pyrite (49.34%) and elemental sulfur (50.72%) but no other sulfur contents were detected. Based on the present results, we speculated that the pyrite forms in coal might affect sulfur biooxidation process.